Amino Acids from Urine as Possible Biomarkers for Early Detection of Vancomycin Nephrotoxicity - †, Harshal R Nanaware; Moorkoth, Sudheer; ††, Nitesh Kumar; Jasphin, Shiny; Raveendran, Arya; Chaudhari, Bhim Bahadur (Indian Journal of Pharmaceutical Education and Research, 2022)
Drug-induced nephrotoxicity is an important therapeutic concern, as many endogenous compounds are filtered through the kidneys for excretion into urine. Vancomycin is a drug of last resort used to treat multiple drug-resistant infections, and is primarily used in paediatrics to treat infections caused by gram-positive organisms resistant to beta-lactam antibiotics. Vancomycin is primarily (80–90%) excreted through the kidney. To identify biochemical markers useful for the early diagnosis of nephrotoxicity, amino acid profiling was performed in young Wistar rats treated with vancomycin. A liquid chromatographymass spectrometry-based method was developed for targeted amino acid analysis from urine samples collected after dosing with vancomycin (300 mg/kg). Alterations in amino acids levels were observed in urine immediately after the first dosing, and increased in prominence during the course of treatment. Nephrotoxicity was confirmed using established methods such as histopathological evaluation and clinical chemistry analysis. Of note, a significant change in amino acid levels in urine was observed well before any noticeable increase in traditional markers. This suggests that quantification of amino acids from urine could be a good alternative to blood-based analysis in neonates and children as a strategy for the detection of kidney injury at an earlier stage than any existing methods.
Keywords: Amino acid profiling; LC-MS; Method validation; Nephrotoxicity; Targeted; analysis; Vancomycin